2005
DOI: 10.2224/sbp.2005.33.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a New Scale: The Reysen Likability Scale

Abstract: While much is known about the concept of likability, a single encompassing tool to measure likability has yet to be created. The Reysen Likability Scale measures the degree of likability for a target source. Using the current scale, a total of 150 participants rated 12 individuals who were videotaped while reading a paragraph. Tapes differed with respect to whether the people genuinely laughed, faked their laughter, or did not laugh while reading a paragraph. In the present study, the reliability, and converge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
144
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 203 publications
(151 citation statements)
references
References 11 publications
3
144
0
4
Order By: Relevance
“…By looking at factors such as friendliness, approachability, attractiveness, levels of knowledge, similarity to oneself, and agreeableness, the Reysen Likeability Scale attempts to measure the likeability of a person. He noted that the more agreeable people are, the more they are likely to rate the individuals as likeable (Reysen, 2005). In our brand likeability scale, we confirmed several of these aspects, but further extended the scale to four dimensions.…”
Section: Brand Likeabilitysupporting
confidence: 77%
See 4 more Smart Citations
“…By looking at factors such as friendliness, approachability, attractiveness, levels of knowledge, similarity to oneself, and agreeableness, the Reysen Likeability Scale attempts to measure the likeability of a person. He noted that the more agreeable people are, the more they are likely to rate the individuals as likeable (Reysen, 2005). In our brand likeability scale, we confirmed several of these aspects, but further extended the scale to four dimensions.…”
Section: Brand Likeabilitysupporting
confidence: 77%
“…Our research has attempted to provide insights into the concepts that explain likeability and a starting 17 point for a sought after conceptualization that captures the domains of the construct of brand likeability (Nguyen, Choudhury, and Melewar, 2014;Reysen, 2005). As we focus specifically on likeability in consumer-brand relationships, investigating consumer perceptions, of which likeability may have a spill-over effect and seen as a brand personality trait (Lee, 2013), we have developed an exploratory study to study brand likeability in-depth using a qualitative study (Nguyen et al, 2013a; we have developed an integrated framework of brand likeability with suggested antecedents and consequences , and finally, we have constructed and tested a brand likeability scale to measure the likeability of firm-level brands (Nguyen, Ekinci, Simkin, and Melewar, 2014).…”
Section: Brand Likeabilitymentioning
confidence: 99%
See 3 more Smart Citations